Rizal for our time essays in interpretation - San Juan, Epifanio 1938- ([S.l.] [s.n.], 1996)
Unpublished compilation of essays about Jose Rizal.
Toward Rizal: a re-interpretation -- From the perspective of today's revolution -- Rizal and the human condition : some preliminary notes -- The sexual fix in Memorias de un estudiante de Manila by P. Jacinto -- Narcissus vanquished : symbolic action in "El ultimo adios" -- Dialectics and history : power, knowledge, agency in Rizal's discourses -- Ideology, class consciousness, history : a reading of Rizal's novels -- Diyalekta at materyalismong pangkasaysayan sa diskurso ni Jose Rizal.
Some leaves photocopied from original publication.
In English except one essay in Filipino.
Keywords: Rizal, Jose -- 1861-1896.; Rizal, Jose -- 1861-1896 -- Criticism and interpretation; Rizal, José -- 1861-1896. -- Criticism and interpretation